2013
DOI: 10.1175/jtech-d-12-00232.1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Accuracy of Surface Humidity Reports*

Abstract: Until recently surface humidity was predominantly measured using psychrometers (wet-and dry-bulb thermometers). In some countries, often in conjunction with increased automation, the measurement technique has changed-usually to capacitive sensors. The scale of the change in instrumentation and the error characteristics of the operational instruments have not been well documented. This paper provides an overview of these operational instruments and their error characteristics, intended to be useful for climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…One is of the type HMP110 (Vaisala, Vantaa, Finland), which is commonly used [41] and often referred to, and a sensing element Rapid P14 (Innovative Sensor Technology, Ebnat-Kappel, Switzerland).…”
Section: Sensors Installed For Humidity Measurementsmentioning
confidence: 99%
“…One is of the type HMP110 (Vaisala, Vantaa, Finland), which is commonly used [41] and often referred to, and a sensing element Rapid P14 (Innovative Sensor Technology, Ebnat-Kappel, Switzerland).…”
Section: Sensors Installed For Humidity Measurementsmentioning
confidence: 99%
“…In a separate field study, Ingleby et al . () found that Rotronics Hydroclip sensors tend to drift by +1% to +2% per year at Met Office sites (although there is a lot of variability) and can be slow to recover from periods stuck at saturation. They estimate that an uncertainty of 2–3% for an operational Rotronics Hydroclip is achievable under best conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Over time they can ‘drift’, especially when exposed to long periods of high humidity, and they have a tendency to read higher (and thus ‘wetter’) by around 1–2% per year (Visscher and Kornet, ). This problem of drift is not isolated to amateur sensors; it occurs in professional systems as well (Ingleby et al ., ), the difference being that professional stations are regularly subject to recalibration using specialised equipment, which is rarely available to amateurs. Even a simple zero‐check for thermometers in iced water proves difficult, as many of the thermometers used in automated amateur weather stations are mounted on a circuit board, which can easily be damaged when submerged in water.…”
Section: The Challenges Facing Amateur Meteorologistsmentioning
confidence: 99%